"Your Faith has Healed You": Christian Orthodox Theology's Ethical Consideration on Placebos. Issue 1 (2nd January 2023) - Mavropoulos, Angelos
ABSTRACT: Although there is no consensus on how placebos actually work, their association with the concept of faith is considered to play a key role. In modern medicine, the traditional use of placebos raises bioethical concerns, despite the fact that it has shown extremely positive results over time. Orthodox Christian moral theology has not yet divulged its views on the matter, although several of its Church Fathers and secular theologians have evaluated the concepts of falsehood, autonomy, and, of course, faith. Thus, by examining these notions, could we conclude the morality of the practice, from the point of view of Christian Orthodox bioethics? This is the question this paper will answer to.